Drivers of Cloud Computing Adoption in Small Medium Enterprises of Indonesia Creative Industry - Gui, Anderes; Fernando, Yudi; Shaharudin, Muhammad Shabir; Mokhtar, Mazita; Karmawan, I Gusti Made; Suryanto, - (JOIV : International Journal on Informatics Visualization, 2021)
Cloud computing is one of the enablers of Industrial Revolution 4.0 (IR.40). IR 4.0 is advantageous as it allows companies to increase performance and productivity. However, there are many enablers of IR 4.0, such as big data analytics, cloud computing, machine learning, and blockchain. However, the readiest to be used technology is cloud computing. While the advantages of cloud computing are well understood from the perspective of the literature and companies' point of view, the empirical evidence is still scarce. The research explores the drivers of cloud adoption between small and medium-sized enterprises (SMEs) in Indonesia. The study method is a quantitative method through e-survey data collection analyzed using IBM SPSS and Smart PLS software. The recognition of drivers will allow IT decision-makers to design the right platform for SMEs, increasing their company competitiveness. The findings revealed that cloud flexibility, perceived concern, privacy, relative advantage, perceived cost-benefit, quality of service, and top management support are among the top cloud adoption priorities that need to be improved in the creative industry to ensure the adoption of cloud computing more apparent. The study's contribution revealed that cloud computing is no longer at the infant stage in terms of adoption. Thus, the findings paved the way for scholars to undertake future research focusing on cloud computing implementation. Companies, on the other hand, can learn from this research by improving the adoption aspects.